Analisis Laju Pertumbuhan Kepiting Bakau (Scylla Serrata) Pada Apartemen Hasil Tangkapan Nelayan Sungai Selindung - Supriyadi, Apri; Pratiwi, Fika Dewi; Salim, Kurniawan (Akuatik: Jurnal Sumberdaya Perairan, 2024)
Mangrove crabs (Scylla serrata) and (Scylla tranqueberica) are species that live in mangrove ecosystems. Mangrove ecosystems have a very important role for mangrove crabs, namely as habitat, foraging and spawning grounds. Mangrove crabs can grow and develop in mangrove forests because there are small organisms that become their food. Mangrove crab cultivation is the enlargement of mangrove crabs that are not ready for production using the container method. The container method is the maintenance and enlargement of mangrove crabs using multilevel containers, one of which is to make it easy to control the growth of mangrove crabs this study aims to analyze the growth rate of mangrove crabs (Scylla serrata) in the apartment caught by Selindung River fishermen for eight weeks. Parameters observed included absolute weight growth, absolute carapace width, and water quality such as salinity, temperature, pH, and dissolved oxygen levels. The results showed that the absolute weight growth of male and female crabs was significantly different, with male crabs having an average carapace width of 104 mm and female crabs 54 mm. This growth is influenced by the moulting process, where the crabs replace the old carapace with a new, larger one. The study found that feeding frequency greatly influenced the growth of carapace weight and width. Specific Growth Rate (SGR) of male crabs was highest at 1.14% per day, while females reached 0.75% per day. Male crabs showed a faster growth rate than females, due to higher metabolic activity. Mangrove crab survival rate reached 100%, indicating the apartment method was effective in supporting growth and survival. During the study, water quality remained in optimal condition with salinity of 27-29‰, temperature of 30-33℃, pH 6.1-6.8, and DO 5.5-6.3 mg/L. In conclusion, the apartment system for mangrove crab aquaculture is effective in improving the growth and survival of mangrove crabs in Selindung River.